Stress-induced cortisol response is associated with right amygdala volume in early childhood - Carina H. Fowler; Ryan Bogdan; Michael S. Gaffrey (Neurobiology of Stress, 2021)
Rodent research suggests that dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis and the resulting cortisol stress response can alter the structure of the hippocampus and amygdala. Because early-life changes in brain structure can produce later functional impairment and potentially increase risk for psychiatric disorder, it is critical to understand the relationship between the cortisol stress response and brain structure in early childhood. However, no study to date has characterized the concurrent association between cortisol stress response and hippocampal and amygdala volume in young children. In the present study, 42 young children (Mage = 5.97, SD = 0.76), completed a frustration task and cortisol response to stress was measured. Children also underwent magnetic resonance imaging (MRI), providing structural scans from which their hippocampal and amygdala volumes were extracted. Greater cortisol stress response was associated with reduced right amygdala volume, controlling for whole brain volume, age, sex, and number of cortisol samples. There were no significant associations between cortisol stress response and bilateral hippocampus or left amygdala volumes. The association between right amygdala volume and cortisol stress response raises the non-mutually exclusive possibilities that the function of the HPA axis may shape amygdala structure and/or that amygdala structure may shape HPA axis function. As both cortisol stress response and amygdala volume have been associated with risk for psychopathology, it is possible that the relationship between cortisol stress response and amygdala volume is part of a broader pathway contributing to psychiatric risk.